Dynamics of Cellular Plasticity in Prostate Cancer Progression - Tiwari, Ritika; Manzar, Nishat; Ateeq, Bushra (Frontiers in Molecular Biosciences, 2020)
Despite the current advances in the treatment for prostate cancer, the patients often develop resistance to the conventional therapeutic interventions. Therapy-induced drug resistance and tumor progression have been associated with cellular plasticity acquired due to reprogramming at the molecular and phenotypic levels. The plasticity of the tumor cells is mainly governed by two factors: cell-intrinsic and cell-extrinsic. The cell-intrinsic factors involve alteration in the genetic or epigenetic regulators, while cell-extrinsic factors include microenvironmental cues and drug-induced selective pressure. Epithelial-mesenchymal transition (EMT) and stemness are two important hallmarks that dictate cellular plasticity in multiple cancer types including prostate. Emerging evidence has also pinpointed the role of tumor cell plasticity in driving anti-androgen induced neuroendocrine prostate cancer (NEPC), a lethal and therapy-resistant subtype. In this review, we discuss the role of cellular plasticity manifested due to genetic, epigenetic alterations and cues from the tumor microenvironment, and their role in driving therapy resistant prostate cancer.